VALUE ORIENTATIONS OF PROFESSIONAL EDUCATION OF A FUTURE MEDICAL WORKER - Victor A. Lazarenko; Natalya N. Savelyeva; Olga V. Parakhina (Высшее образование в России)
This article deals with the results of a theoretical research and analysis of education practice at medical education establishments, which became the base for development and realization of the program of professional education of future medical workers.